2023
DOI: 10.1001/jamanetworkopen.2023.9316
|View full text |Cite
|
Sign up to set email alerts
|

Association of Health-Related Social Needs With Quality and Utilization Outcomes in a Medicare Advantage Population With Diabetes

Abstract: ImportanceRecent research highlights the association of social determinants of health with health outcomes of patients with type 2 diabetes (T2D).ObjectiveTo examine associations between health-related social needs (HRSNs) and health care quality and utilization outcomes in a Medicare Advantage population with T2D.Design, Setting, and ParticipantsThis cross-sectional study used medical and pharmacy claims data from 2019. An HRSN survey was given between October 16, 2019, and February 29, 2020, to Medicare Adva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…We can extrapolate from adult data the effect of FI on health-care utilization. Adult DM studies demonstrated similar findings of increased health-care utilization, emergency visits, inpatient encounters, avoidable hospitalizations, and significantly higher annual health-care expenditures relative to those who are not food insecure [ 54 ] and increased nonadherence to DM medication with an adjusted odds ratio of 23.92 times higher compared to those who were food secure [ 55 ].…”
Section: Factors Influencing Health-care Utilization In Young Adultsmentioning
confidence: 98%
“…We can extrapolate from adult data the effect of FI on health-care utilization. Adult DM studies demonstrated similar findings of increased health-care utilization, emergency visits, inpatient encounters, avoidable hospitalizations, and significantly higher annual health-care expenditures relative to those who are not food insecure [ 54 ] and increased nonadherence to DM medication with an adjusted odds ratio of 23.92 times higher compared to those who were food secure [ 55 ].…”
Section: Factors Influencing Health-care Utilization In Young Adultsmentioning
confidence: 98%
“…47,48 Social factors such as limited access to regular care, insurance, or health literacy may increase the propensity for patients to use acute or urgent care services, thereby increasing the number of prescribers. 49 Given the increased number of specialists per patient, deprescribing interventions must carefully consider the complexity of interpersonal and organizational variables that can influence successful deprescribing. Financial pressures to adhere to disease-focused quality metrics and pay-for-performance models can hinder the identification of potentially unnecessary medications and the associated development of deprescribing solutions.…”
Section: Societal Levelmentioning
confidence: 99%
“…Furthermore, evidence‐based guidelines often focus on the management of a single disease rather than multiple chronic conditions, which can contribute to undetected harms when patients with coexisting comorbidities are being treated by multiple specialists 47,48 . Social factors such as limited access to regular care, insurance, or health literacy may increase the propensity for patients to use acute or urgent care services, thereby increasing the number of prescribers 49 …”
Section: Barriers To Deprescribing In the Presence Of “Multiple Presc...mentioning
confidence: 99%
“…Research has shown that having unmet basic needs, such as food insecurity, is associated with adverse diabetes-related clinical outcomes and poorer access to and quality of care (Berkowitz et al, 2015; Cole Nguyen, 2020; Fitzpatrick, Banegas, Kimes, Papajorgji-Taylor, Fuoco, 2021; Gold et al, 2022; Gucciardi, Vahabi, Norris, Del Monte, Farnum, 2014; Ryan et al, 2023). Furthermore, individuals with food insecurity are significantly more likely to have frequent emergency department (ED) utilization than individuals who are food-secure (Estrella et al, 2021).…”
Section: Introductionmentioning
confidence: 99%